Women Working the NAFTA Food Chain: Women, Food and Globalization - Barndt, Deborah; Harjo, Joy; Friedmann, Harriet; Reiter, Ester; Martinez-Salazar, Egla; Baron, Antonieta; Appendini, Kirsten; Ansley, Fran; Eyerman, Ann; Kainer, Jan; Field, Debbie; Villagomez, Maria Dolores; et al. (Second Story Press, 1999)
This collection of compelling and original research makes connections in Canada, the US and Mexico among women who work in fast-food restaurants, supermarkets and agricultural production. The fourteen chapters take a critical look at how the North American Free Trade Agreement (NAFTA) has affected these women's working and living conditions, sharpening our understanding of how the workplace has been restructured in order to fulfill consumer demands for tomatoes, exotic flowers and fruits, as well as fast-food burgers and fries. Food activists in Latin America, the US and Canada propose alternatives to counteract the oppressive conditions of free trade and globalization. –Publisher's description. Contents: "Perhaps the world ends here" / Joy Harjo – Introduction: In the belly of the beast: A moveable feast / Deborah Barndt – Remaking "traditions": How we eat, what we eat and the changing political economy of food / Harriet Friedmann – Whose "choice"?: "Flexible" women workers in the tomato food chain / Deborah Barndt – Serving the McCustomer: Fast food is not about food / Ester Reiter – The "poisoning" of Indigenous migrant women workers and children: From deadly colonialism to toxic globalization / Egla Martinez-Salazar – Mexican women on the move: Migrant workers in Mexico and Canada / Antonieta Barrón – "From where have all the flowers come?": Women workers in Mexico's non-traditional markets / Kirsten Appendini – Putting the pieces together: Tennessee women find the global economy in their own backyards / Fran Ansley – Serving up service: Fast-food and office women workers doing it with a smile / Ann Eyerman – Not quite what they bargained for: Female labour in Canadian supermarkets / Jan Kainer – Putting food first: Women's role in creating a grassroots system outside the marketplace / Debbie Field – Grassroots responses to globalization: Mexican rural and urban women's collective alternatives / Maria Dolores Villagomez – Women as organizers: Building confidence and community through food / Deborah Moffett & Mary Lou Morgan – A day in the life of Maria: Women, food, ecology and the will to live / Ofelia Perez Peña – A different tomato: Creating vernacular foodscapes / Lauren Baker.
https://www.canadianscholars.ca/books/women-working-the-nafta-food-chain#tab_overview